The Implementation of Minister of Health Regulation on Performance Improvement in Individual and Community Health Service (Study of Puskesmas Bawen, Central Java) - Hidayati, Selvia Ichwani (JILS (Journal of Indonesian Legal Studies), 2018)
One of public services implemented by the government is the fulfillment of public health needs. Health reform is implemented to improve health services that make it more efficient, effective and accessible to all levels of society. Towards a better and overall health insurance, the government issued Law No. 40 on the National Social Security System whereby Health Insurance is a priority that will be developed to achieve the participation of Universal Health Coverage (UHC). This paper discusses the implementation and constraint in the implementation of improving the health services performance in individual and community health services at Bawen Public Health Center (Puskesmas, Pusat Kesehatan Masyarakat). The author argued that the implementation of improving the Public Health Center performance in individual and societal health services perspective Minister of Health Regulation Number 71 of 2013 at Bawen Public Health Center has been running in accordance with the implementation indicators, but there are still some problems internally and externally that is late drugs provision that inhibit delivery Service. In addition, the attitude and clarity in providing information needs improvement.